Students Perception Regarding the Use of ChatGPT in Semantics Class at Universitas Bhinneka PGRI - Zalza Devika Widiyananda; Erna Dwinata (JURNAL PENDIDIKAN BAHASA, 2025)
This study aims to explore students' perceptions regarding the use of ChatGPT in the Semantics course at Universitas Bhinneka PGRI. The research was motivated by the rapid advancement of artificial intelligence (AI) technology, particularly in the field of education. A descriptive qualitative method was employed, with data collected through open-ended questionnaires and semi-structured interviews. The participants were sixth-semester students of the English Education Department who had taken the Semantics course. The findings revealed that most students had positive perceptions toward the use of ChatGPT, especially in simplifying semantic concepts and promoting independent learning. Some challenges were also identified, including, including the risk of over-reliance, limited digital literacy, and the possibility of inaccurate information. Based on these findings, this study suggests the need for digital literacy training and responsible integration strategies to ensure that ChatGPT is used effectively to support the learning process.